The regulatory actions of retinoic acid on M2 polarization of porcine macrophages. (September 2019) - Chen, Celine; Perry, Trinity L.; Chitko-McKown, Carol G.; Smith, Allen D.; Cheung, Lumei; Beshah, Ethiopia; Urban, Joseph F.; Dawson, Harry D.
Abstract: We previously demonstrated that the most bioactive vitamin A metabolite, all-trans retinoic acid (ATRA), increased T helper 2-associated responses induced in pigs by infection with the parasitic nematode Ascaris suum We also showed that ATRA potentiated the mRNA expression of several IL-4 induced chemokines (chemokine (CC motif) ligand 11 [(CCL11), CCL17, CCL22 and CCL26] associated with alternative activation (M2a) in porcine macrophages in vitro . Herein, several mechanisms whereby ATRA affects IL-4 signaling are profiled using large-scale real time PCR and RNA-Seq analysis. Twenty-three genes associated with M2a markers in other species were independently upregulated by both IL-4 and ATRA, including the adenosine receptor A2B (ADORA2B), cysteinyl leukotriene receptor 2 (CYSLTR2) and the vitamin D receptor (VDR). ATRA synergistically enhanced IL-4 up-regulation of Hepatitis A virus cellular receptor 2 (HAVCR2) and transglutaminase 2 (TGM2) and further repressed IL-4 down-regulated CD163 and Cytochrome b-245, beta polypeptide (CYBB) mRNA. Macrophages treated with ATRA exhibited a dose-dependent reduction in phagocytosis of opsonized Staphylococcus aureus . In addition, the combination of IL-4 and ATRA up-regulated the anti-inflammatory protein, IL-1R antagonist (IL1RN) and TGM2. These data indicate that ATRA induces a state of partial alternative activation in porcine macrophages, and amplifies certain aspects of M2a activation induced by IL-4. Given the prevalence of allergic and parasitic diseases worldwide and the close similarities in the porcine and human immune responses, these findings have important implications for the nutritional regulation of allergic inflammation at mucosal surfaces. Highlights: We identified 23 mRNA that are independently induced by both RA and IL-4 associated with the M2 activation state. We also identified 18 additional mRNA that increase or decrease synergistically, when macrophages are exposed to IL-4 and RA. We observed a reduction in phagocytosis of Staphylococcus aureus, in cells treated with either IL-4 or RA. We observed that combination of RA and IL-4 induced the interleukin 1 receptor antagonist and the M2a marker, TGM2, proteins.